Stranded and seduced - Grayson, Emmy (Harlequin presents, 2024)
"Griffith Lykaois has rejected his family's billion-dollar legacy. It's a fitting punishment for his guilt over his father's death. Only, estate lawyer Rosalind Sutton won't quit. Amid a raging storm, the infuriatingly alluring woman is on his remote château doorstep determined he claim his inheritance. Rosalind needs Griffith's signature; the career she put her life on hold for depends on it. But stranded alone with the brooding tycoon, there's no way innocent Rosalind can escape her response to their intoxicating clashes... The question is, does Rosalind even want to? "--